Imaging measures of molecular pathology and neurodegeneration in dominantly‐inherited and sporadic early‐onset Alzheimer's Disease. (1st February 2022) - Iaccarino, Leonardo; Llibre‐Guerra, Jorge J.; Edwards, Lauren; Mundada, Nidhi; Strom, Amelia; Tsoy, Elena; Li, Yan; Gordon, Brian A.; Schindler, Suzanne E.; Fagan, Anne M.; Benzinger, Tammie L.S.; Wang, Guoqiao; et al.
Abstract: Background: Approximately 5% of patients with Alzheimer's Disease (AD) develop symptoms before age 65, with this early‐onset presentation attributed to either sporadic (sEOAD) or dominantly‐inherited (DIAD) etiology. Both sEOAD and DIAD are characterized by brain amyloid‐beta (Aβ) accumulation and neurodegeneration, but differences in topography and magnitude of these pathological changes are not fully elucidated. Method: We included 108 sEOAD Aβ‐PET positive cases from the UCSF Alzheimer's Disease Research Center (mean±standard deviation age 59.7±5.4 years) and 86 DIAD cases from the Dominantly Inherited Alzheimer Network (DIAN) study (age 45.5±9.5 years) with symptom onset before 65 years (see Table 1). All cases were symptomatic (clinical dementia rating [CDR] global ≥0.5) and underwent standard clinical and cognitive measures, 11 C‐PiB‐PET (Aβ), 18 F‐FDG‐PET (glucose metabolism) and structural MRI. PET scans were processed to obtain Standardized Uptake Value Ratio (SUVR, PIB50‐70, FDG30‐60 ) images. Warped PET SUVR and modulated, warped gray matter images were compared across the two cohorts with SPM12 after smoothing to ∼8mm 3, covarying for age, CDR sum of boxes, years of education, APOE e4 status, and respective global biomarker score. A‐priori statistical threshold was set at p<0.001 uncorrected, with a Family Wise Error p<0.05 correction at the cluster‐level. Result: sEOAD participants were older, more educated, had greater cognitive impairment, had higher Aβ burden and were more likely to be APOE ε4 carriers (see Table 1). sEOAD participants exhibited higher relative PIB‐PET binding in anterior temporal and frontal (mostly white matter) regions, as well as lower relative FDG‐PET binding and sMRI‐based volumes in temporoparietal regions. DIAD participants showed higher relative PIB‐PET binding in the medial occipital, thalami, basal ganglia (caudate nuclei and putamen) and medial/dorsal frontal regions. DIAD participants showed lower relative FDG‐PET binding mostly in the frontal and parietal white matter (see Figure 1). Conclusion: Aβ pathology in DIAD was more likely to affect subcortical systems, whereas both Aβ pathology and neurodegeneration tended to be relatively more cortical and extensive in sEOAD. These results highlight EOAD heterogeneity and show that sporadic and inherited AD exhibit distinct regional vulnerabilities in neurodegeneration as well as differing topography and magnitude of biomarker abnormalities.